The health and wellbeing of Australian farmers: a longitudinal cohort study - Bronwyn Brew; Kerry Inder; Joanne Allen; Matthew Thomas; Brian Kelly (BMC, 2016)
Abstract Background Isolation, long work days, climate change and globalization are just some of the many pressures that make farming a vulnerable occupation for incurring mental health issues. The objective of this study was to determine whether farming in Australia is associated with poorer wellbeing, physical and mental health, and less health service use. Methods The Australian Rural Mental Health Study, a longitudinal cohort study was analysed over four time points comparing farmers with non-farming workers (n = 1184 at baseline). Participants were recruited from rural NSW, Australia. A number of physical, mental health, wellbeing, service use outcomes were assessed using generalised estimating equations including all waves in each model. Barriers to seeking help were also assessed. Results Farmers who lived remotely reported worse mental health (β −0.33, 95 % CI −0.53, −0.13) and wellbeing (β −0.21(95 % CI −0.35, −0.06) than remote non-farm workers regardless of financial hardship, rural specific factors eg drought worry, or recent adverse events. All farmers were no different to non-farming workers on physical health aspects except for chronic illnesses, where they reported fewer illnesses (OR 0.66, 95 % CI 0.44, 0.98). All farmers were half as likely to visit a general practitioner (GP) or a mental health professional in the last 12 months as compared to non-farm workers regardless of location (OR 0.59, 95 % CI 0.35, 0.97). Rural workers felt that they preferred to manage themselves rather than access help for physical health needs (50 %) or mental health needs (75 %) and there was little difference between farmers and non-farm workers in reasons for not seeking help. Conclusions Remoteness is a significant factor in the mental health and wellbeing of farmers, more so than financial stress, rural factors and recent adverse events. Creative programs and policies that improve access for farmers to GPs and mental health professionals should be supported.